2019
DOI: 10.1111/wvn.12401
|View full text |Cite
|
Sign up to set email alerts
|

What Do Nurses Need to Practice Effectively in the Hospital Environment? An Integrative Review With Implications for Nurse Leaders

Abstract: Background When staffing legislation was introduced, New Jersey nurse leaders recognized from the research and their years of clinical leadership experience that the work environment is a multidimensional concept and that staffing is not the only variable related to nurse and patient outcomes. Thus, an understanding of what nurses need in their hospital environment to practice nursing effectively was sought. Aims The aim of this study was to examine the evidence regarding clinical nurses’ perception of what th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 38 publications
1
39
0
7
Order By: Relevance
“…Every healthcare system has its own culture with elements that serve to both facilitate and prevent leadership expression at the bedside. Kowalski et al, (2020) found that a culture that promotes a healthy work environment provides an atmosphere in which leadership, teamwork, and organisational commitment to nursing, among other characteristics, allows nurses to deliver high‐quality care. Many of these characteristics of a healthy work environment were identified by our focus group participants as facilitators of their leadership at the bedside.…”
Section: Discussionmentioning
confidence: 99%
“…Every healthcare system has its own culture with elements that serve to both facilitate and prevent leadership expression at the bedside. Kowalski et al, (2020) found that a culture that promotes a healthy work environment provides an atmosphere in which leadership, teamwork, and organisational commitment to nursing, among other characteristics, allows nurses to deliver high‐quality care. Many of these characteristics of a healthy work environment were identified by our focus group participants as facilitators of their leadership at the bedside.…”
Section: Discussionmentioning
confidence: 99%
“…Staff nurses are closely involved in providing care to their patients but are not constantly involved in decisions affecting the delivery of care. Kowalski et al (2020) identified that nurses value work environments with effective leadership that fosters decision-making, autonomy in nursing practice, respect, teamwork, and cohesive interactions.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Shared governance, participative decision-making, open communication, shared vision, self-reflection, and a fair and respectful working atmosphere that conveys appreciation and gratitude to nurses and their positions are popular strategies that enhance the efficacy of leadership, promote positive work attitudes among nurses, and achieve desired results (Abou Hashish, 2020;Abou Hashish & Fargally, 2018;Kowalski et al, 2020). Nurse managers should create opportunities for training and learning to inspire resilient and assertive nurses.…”
Section: Implications Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the nursing work environment in the emergency department is a busy and complex environment in which various professional staff members have both horizontal and vertical relationships [14]. Leadership, response/teamwork, and resourcing are especially important to provide high-quality care in this nursing environment [15], and in this organizational system, the head nurse is the most frequent contact in the vertical relationships of emergency department nurses. Although there has been no study on the relationship between posttraumatic growth and relationship with the head nurse, a previous study focusing on the relationship between leaders and members showed the perceived quality of exchange relations of staff nurses with head nurses is a more important factor influencing nurses' job satisfaction and organizational commitment than the quality of exchange relations of head nurses [16].…”
Section: Introductionmentioning
confidence: 99%